SUBSTITUSI EKSTRAK KULIT BUAH NAGA MERAH TERHADAP PEMBUATAN KULIT KUE DADAR GULUNG - Juni Karmila; Windy Della Sari (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2021)
This article reports the finding of whether or not red dragon fruit peel extract can be substituted for the green color previously used from pandan and suji leaf extracts for the skin of rolled pancakes. The rationale is that people in general still make red dragon fruit peel as unused waste. It actually contains antioxidants that function against oxidation and antimicrobial activity. It also contains bettasianin which functions as a natural red dye as an alternative substitute for synthetic color in rolled pancakes. Therefore, to be able to take advantage of the dragon fruit peel, it can be utilized as the skin of rolled pancakes to get a more attractive appearance. The research method used was the experimental method to find out the effect of certain treatments. Data obtained through the organoleptic test by distributing questionnaires to the panelists. The results showed that rolled pancakes with a substitution of 50% red dragon fruit peel extract had quite a dragon fruit aroma, was pink in color, with a very porous texture, and had a dragon fruit taste. Rolled pancake with 70% substitution had a red dragon fruit aroma, was very pink in color, and had a porous texture.